Content Analysis on Cultural Context of Junior High School English Textbook - Lembah, Sri Ulfa Dwi Yana; Jusuf, Harni; Ismail, Abdul Kadir (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
Textbooks have important roles in learning, including learning English. English textbooksare not only a source of information about the material studied but also provide anoverview of the culture contained in the textbook. Concerning to culture, this researchaims to determine the culture portrayed in the English textbook "Think Globally ActLocally" used by SMP MUHAMMADIYAH 2 Gorontalo students in Grade IX and todetermine the teacher’s way to implement the culture in textbooks. This research usedqualitative descriptive. The data collected through observation check list, interview, anddocumentation. The steps in analyzing the data are: (1) reading the textbook "ThinkGlobally Act Locally"; (2) grouping culture into several aspects according to the theoryused by Cortazzi and Jin and Adaskou, Briten and Fahsi; (3) analyzing the most dominantculture in textbooks. The research findings shown that the culture described in textbooksincludes source culture, target culture and international culture. The culture that appearsmost often is the source culture. This is evidenced by the results of 50% source culture, 38% target culture and 12% international culture.Keywords: Textbooks, Cultural, Source Culture, Target Culture, International Culture